PERAN KOMITMEN ORGANISASIONAL DALAM MEMEDIASI PENGARUH STRES KERJA TERHADAP INTENSI KELUAR PERAWAT DI RUMAH SAKIT XYZ - Justicia Purba, Elisabeth Marcella; Supartha, Wayan Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.03.TAHUN.2025, 2025)
The purpose of this study was to explain the role of organizational commitment in mediating the effect of work stress on nurse turnover intention. The research was conducted on nurses at XYZ Hospital Bandung. The number of research samples was 98 people, which were taken using the proportional random sampling method. Data was collected by interviews and distributing questionnaires. The data analysis technique used path analysis. The results showed that work stress has a positive and significant effect on nurse’s turnover intentions. Work stress has a negative and significant effect on nurse’s organizational commitment. Organizational commitment has a negative and significant effect on nurse’s turnover intentions. The results of the mediation test showed that organizational commitment significantly mediated the effect of work stress on nurse’s turnover intentions. The implication of this research is to prove the theory of reasoned action and its relation to research variables. These results illustrate that with sufficient organizational commitment can reduce the level of work stress of nurses, so that turnover intentions can also decrease.